Natural diet of the freshwater prawn Macrobrachium amazonicum (Heller, 1862) in the Rio Grande, southeastern Brazil - da Cruz, Barbara Regina Fernandes; Nogueira, Caio Santos [UNESP]; Bueno, Alessandra Angélica Pádua; Jacobucci, Giuliano Buzá (Taylor & Francis, 2024)
Macrobrachium amazonicum (Heller, 1862) is a freshwater prawn species subject to high commercial exploitation in northern Brazil, with wide geographic distribution and high phenotypic plasticity. This study aimed to assess the natural diet of an M. amazonicum population from Rio Grande, comparing consumed items with differences according to sex, seasons, and habitat food availability. The prawns were collected monthly between September 2018 and August 2019. A total of 348 stomachs were examined, and their content evaluated based on degree of repletion, the point method, and frequency of occurrence. Food preferences were also determined. Seven food types were recorded in the stomachs of M. amazonicum, including microplastics. No significant differences were observed in the diet between males and females or across different seasons. The species exhibited no food preference in its diet. The findings confirm an omnivorous diet for M. amazonicum and suggest that the composition and proportion of dietary items may depend on their availability in the environment. The presence of microplastics in the analyzed stomachs raises concern as it indicates contamination in the aquatic environment resulting from unsustainable human activities.
Keywords: Amazon river prawn; feeding habits; Palaemonidae; plastic pollution